Solid Earth Uplift Due To Contemporary Ice Melt Above Low-Viscosity Regions of the Upper Mantle - Weerdesteijn, Maaike Francine Maria; Conrad, Clinton Phillips; Naliboff, John B. (Geophysical Research Letters, 2022)
Glacial isostatic adjustment explains topographic change in formerly and currently glaciated regions, but the role of small (∼100s km) regions of unusually low-viscosity mantle is poorly understood. We developed viscoelastic models with low-viscosity regions in the upper mantle, and measured the effect of these regions on solid earth uplift resulting from contemporary surface ice melt. We found viscous uplift occurring on decadal timescales above the low-viscosity region, at rates comparable to or larger than those from elastic uplift or the viscous response to ice age melting. We find that uplift rates are sensitive to the location, dimensions, and viscosity of the low-viscosity region, and that the largest uncertainty in uplift rates likely comes from the low-viscosity region's horizontal extent. Rapid viscous ground uplift can impact ice dynamics if the low-viscosity region is located close to an ice sheet margin, as for Antarctica and Greenland. Solid Earth Uplift Due To Contemporary Ice Melt Above Low-Viscosity Regions of the Upper Mantle